The Nexus Between The Character Of Independence And Entreprenuership Learning Subject: Case Study Faculty Of Training And Education Lambung Mangkurat University - Adawiyaha, Raudatul; Ratumbuysang, Monry Fraick Nicky Gillian; Hasanah, Mahmudah; Atmono, Dwi (inovator, 2023)
The issues that can be formulated based on the context mentioned above are as follows: 1. How is the description of the character of independence and entrepreneurship learning in FKIP students at Lambung Mangkurat University? 2. Is there a relationship between the character-building of student independence and entrepreneurship learning? This study aims to analyze the relationship between the character of independence with entrepreneurship learning courses: a case study of the Faculty of Teacher Training and Education, Lambung Mangkurat University. The method used in this research is a descriptive quantitative approach using ex post facto method. The research subjects consisted of 338 students from all students of the Faculty of Teacher Training and Education Banjarmasin who had taken entrepreneurship courses, data collection techniques using online questionnaires for validity and reliability tests, data analysis using descriptive analysis techniques and simple linear correlation. Based on the results of the study, it shows that the relationship between the formation of student independence character with entrepreneurship learning at Lambung Mangkurat University as a whole is still relatively low. This is obtained from the correlation coefficient value of 0.336 with a significance value/p-value of 0.000, because the significance value of p t table 1.967, so it can be concluded that H1 is accepted which means there is a relationship between Character Independence (X) and Entrepreneurship Learning (Y). Future research is expected to provide deeper knowledge and explore further the character of independence in building student relationships. This research is considered different from existing research and is the latest research that combines two variables, namely the character of independence and entrepreneurship learning.